2019
DOI: 10.1002/kjm2.12028
|View full text |Cite
|
Sign up to set email alerts
|

Low‐dose midazolam and propofol use for conscious sedation during diagnostic endoscopy

Abstract: To find the right sedation technique for different types of treatment methods and the right amount of sedatives so the chances of side effects happening can be reduced. This was a retrospective cohort analysis conducted on prospectively collected data. Patients who underwent esophagogastroduodenoscopy only (E group) were sub‐divided into two subgroups: (a) Those who received 0.5 mg/kg of propofol (E‐a), (b) Those who received 0.025 mg/kg of midazolam and 0.5 mg/kg of propofol (E‐b). Patients who underwent esop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 36 publications
1
5
0
Order By: Relevance
“…In a prospective multicentre study, including 11,701 gastrointestinal endoscopy patients, Sieg et al [21] found that few cases of hypotension (0.02%), bradycardia (0.05%), and hypoxaemia (0.5%) occurred for a sedation regimen consisting of 2-3 mg midazolam plus 10-20 mg propofol followed by boluses of 20-30 mg propofol. The incidence of side effects related to midazolam combined with propofol was comparable to previous studies, which also used similar propofol and midazolam doses for endoscopy sedation [19][20][21].…”
Section: Discussionsupporting
confidence: 83%
See 2 more Smart Citations
“…In a prospective multicentre study, including 11,701 gastrointestinal endoscopy patients, Sieg et al [21] found that few cases of hypotension (0.02%), bradycardia (0.05%), and hypoxaemia (0.5%) occurred for a sedation regimen consisting of 2-3 mg midazolam plus 10-20 mg propofol followed by boluses of 20-30 mg propofol. The incidence of side effects related to midazolam combined with propofol was comparable to previous studies, which also used similar propofol and midazolam doses for endoscopy sedation [19][20][21].…”
Section: Discussionsupporting
confidence: 83%
“…Be- cause of the lack of analgesic efficacy when used as a single agent during endoscopic sedation, higher doses of propofol are required to maintain the desired level of sedation and increase cardiorespiratory side effects [15,16]. The addition of an opioid and/or midazolam to propofol may help to reduce propofol consumption and, thus, the incidence of side effects [16][17][18][19].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…At present, the sedative drugs used in clinical endoscopy are mainly midazolam and propofol. Midazolam has a long duration of action and slow recovery from anesthesia (6,7). In addition to the injection site pain, propofol also has strong respiratory and circulatory inhibitory effects, thus increasing the incidence of accidental risks such as hypoxemia, hypotension, and cardiac arrest (8,9).…”
Section: Introductionmentioning
confidence: 99%
“…10 When sedating a patient for endoscopy, the aim is moderate sedation. 11,12 However, the level of patient consciousness may vary by operator and patient because the depth of sedation depends on the quantity of sedatives used and the patient's response. 11,13 It is very important to maintain an appropriate level of sedation.…”
Section: Introductionmentioning
confidence: 99%